Time to Move On: The Role of Greenness in Africa and Temperatures at a Mediterranean Stopover Site in Migration Decision of Long-Distance Migratory Passerines - Aharon-Rotman, Yaara; McEvoy, John F.; Kiat, Yosef; Raz, Tal; Perlman, Gidon Y. (Frontiers in Ecology and Evolution, 2022)
Many migratory species have advanced their migration timing as a response to the advanced onset of breeding conditionsseason, mainly in northern latitudes. While data on arrival timing to breeding grounds in Europe is plentiful, information from the African departure sites are scarce. Here we analysed investigated changes in arrival timing of four long-distance migratory passerines to a stopover site in Israel and potential links to Enhanced Vegetation Index (EVI) at the species-specific African pre-departure sites and local temperatures at the stopover site. We found that Lesser whitethroat (Curruca curruca) and Eastern Bonelli’s warbler (Phylloscopus orientalis) advanced arrival to the stopover site. The arrival timing of Thrush nightingale (Luscinia luscinia) and Olive-tree warbler (Hippolais olivetorum) did not change and was associated with mean EVI at the pre-departure site in Africa during the pre-migratory period. Additionally, temperatures at the stopover site affected the arrival timing of Lesser whitethroat only. This is, probably because this species breed at higher northern latitudes and fine-tune their migration timing to match local conditions. Our results show that spring migration can be influenced by exogenous cues such as weather condition and food availability, and the level of response is species-specific. Moreover, some species show flexibility and fine-tuned migration speed in response to local conditions en route. While flexibility seems advantageous, dependence on multiple sites with varying conditions may ultimately limit advanced arrival to the breeding ground and result in mismatch with optimal conditions.